MANAGING THE POROUS BOUNDARIES: IMPACT OF WORKING FROM HOME ON WORK LIFE BALANCE OF UNIVERSITY TEACHERS DURING COVID 19 - Farah Naz; Awan, Riffat-un-Nisa; Dr. Ghazala Noureen (Journal of Arts & Social Sciences, 2021)
The closure of educational institutions due to COVID-19 has forced universities to shift from in-class to online education. We aim to address an aspect of this shift that remains widely unacknowledged, namely, the gender inequalities associated with the struggle to manage two separate domains (home and work) under the same roof. Using cross sectional data gathered through an online survey from various universities and degree awarding institutions, we explore the question of how working from home during the covid-19 pandemic has shifted (or not shifted) the work-life balance of male and female university teachers. Our research shows that work from home during covid-19 has some negative repercussions for the work life balance of female university teachers. Females are facing difficulty in maintaining a healthy work life balance. They reported more work family conflicts; more family demands and challenges; and less satisfaction while working from home as compared to male university teachers. The findings of our paper suggest that this new workplace arrangement has disproportionately increased the overall burden on female university teachers in both the important domains of their life (Family and work). Key Words: COVID-19, Gender, Work from Home, Work Life Balance